Development of Blended Learning-Based Learning Tools to Practice Students' Scientific Argumentation Ability - Pramestya Taranita Widiastuti; Yuliani Yuliani; Raharjo Raharjo (Budapest International Research and Critics University, 2022)
The Covid-19 pandemic has resulted in a shift in the learning model from online to offline. As is the case with science lessons, especially in photosynthesis material where it is necessary to synchronize effective learning models in order to improve the stability of scientific argumentation. The purpose of this study is to produce Blended learning-based learning tools to train students' scientific argumentation skills. This research method uses the 4P method with a trial design using experimental research with the One Group Pretest Postest Design model. The results showed that (1) the learning devices used were included in the very valid category, (2) The practicality of the learning device was obtained from RPP 1 with a percentage of 95% (Online) and from RPP 1 with a percentage of 98% (Offline), and (3) The effectiveness of the learning device was reviewed from the argumentation value and the value of learning outcomes was included in the high category with a score obtained from student responses with a percentage of 94%.